Interaksi Antara Penari Dan Penonton Dalam Pertunjukan Tor-Tor Di Pasar Kamu Kecamatan Pantai Labu - Sabrina Maulidia Putri (Jurnal Riset Rumpun Seni, Desain dan Media, 2024)
This article aims to determine the interactions that exist between dancers and the audience in the Tor-Tor performance at Pasar Kamu, Pantai Labu District. This performance is performed between dancers and the audience by interacting through communication by attracting the attention of the audience to join in dancing together. Research in this article uses qualitative methods with data collection techniques by means of observation, interviews and documentation. The research results show that in the Tor-Tor performance there is social interaction between the public as spectators and the Tor-Tor dancers, and intrapersonal communication is established through movements as conveyance of messages and recipients of messages carried out by the audience and dancers in the Tor-Tor performance. Through this article, it is hoped that it can raise a positive image that traditional dance is worth preserving.